Alternate block shear in beams: Experimental and FE fracture modeling. (1st May 2019) - Helwe, Mazen B.; El Kalash, Sana N.; Hantouche, Elie G.
Highlights: Alternate block shear failure mode is investigated experimentally and mechanically. The geometrical features affecting this failure mode are investigated. Two fracture models, predefined in ABAQUS, are calibrated for all steel material. The pre-yielding and post-yielding responses of the tested specimens are predicted. Abstract: This study investigates experimentally and analytically the alternate block shear (ABS) failure in steel beams. ABS might be a potential failure mode of beams in bolted connections subjected to pure tensile forces. The results of a series of four specimens are presented and discussed. The experimental results showed that the ABS failure path is a combination of both yielding and rupture mechanisms leading to a ductile failure in the beam. Also, the experimental results showed that as the connection length decreases and/or beam depth increases the ABS failure mode governs. The experimental results indicate that the ABS failure have a lower capacity than the classical block shear failure and is a ductile failure mode. Thus, post-yielding strength and ductility are needed to be predicted using finite element (FE) fracture modeling. FE fracture simulations, including tensile and shear fracture modeling, are developed to predict the experimental results after first component failure. The Rice and Tracey and the Hooputra models are associated with all steel materials to model their ductile damage under tensile and shear loading, respectively. Prior to experimental validation, both base and bolt materials are calibrated for stress-strain and stress triaxiality-strain at fracture responses. The results showed that the FE fracture models can predict with acceptable accuracy the experimental results of force-deformation and the behavior and failure path of the tested specimens. The objective of this study is to expand the experimental and numerical database in investigating the ABS failure mode. This study will guide designers to include ABS in the current design procedures as a limit state.